2006
DOI: 10.2478/v10155-010-0081-0
|View full text |Cite
|
Sign up to set email alerts
|

Numerical analysis of the Anderson localization

Abstract: The aim of this paper is to demonstrate, by simple numerical simulations, the main transport properties of disordered electron systems. These systems undergo the metal insulator transition when either Fermi energy crosses the mobility edge or the strength of the disorder increases over critical value. We study how disorder affects the energy spectrum and spatial distribution of electronic eigenstates in the diffusive and insulating regime, as well as in the critical region of the metal-insulator transition. Th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

15
245
0
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 135 publications
(261 citation statements)
references
References 160 publications
(406 reference statements)
15
245
0
1
Order By: Relevance
“…This estimate has been confirmed in subsequent work [10][11][12][13] . Clear demonstrations of the universality of this value include its confirmation in a non-interacting tight-binding model with random hopping of a doped semiconductor 14 , and its experimental measurement in a quasi-periodic atomic kicked rotor 15 .…”
Section: Introductionsupporting
confidence: 77%
“…This estimate has been confirmed in subsequent work [10][11][12][13] . Clear demonstrations of the universality of this value include its confirmation in a non-interacting tight-binding model with random hopping of a doped semiconductor 14 , and its experimental measurement in a quasi-periodic atomic kicked rotor 15 .…”
Section: Introductionsupporting
confidence: 77%
“…Generalized DMPK equation (GDMPK) contains new parameters K ab , which measure the spatial non-homogeneity of electron distribution [9]. Both approximate [9] and numerical [10] solutions of GDMPK equation agree very well with results of numerical simulations [5].…”
Section: Introductionsupporting
confidence: 63%
“…Although the typical transmission through the strongly disordered sample is small, we can find, thanks to large conductance fluctuations [5], the sample with relatively large transmission. Figures 3 and 4 show that the spatial electron distribution is not homogeneous inside the strongly disordered systems.…”
Section: Strongly Localized Limitmentioning
confidence: 99%
See 1 more Smart Citation
“…We found that at length scales corresponding to the transition from diffusive to localized transport, the probability distribution of the dimensionless conductance, g, develops non-analytic behavior around g ≈ 1 [19,20], suggesting transport governed by a single-channel [21][22][23].…”
mentioning
confidence: 94%